Sustainable Food Procurement Legal, Social and Organisational Challenges (Taylor & Francis, 2024)
The book examines sustainable food procurement policy and practice in the European Union and beyond, exploring the extent to which sustainability objectives have been achieved and evaluating the new developments taking place at both EU and national levels. While there is a growing recognition that public authorities can use public procurement as a policy tool to pursue multiple environmental, health and socio-economic objectives, contracting authorities still face many challenges. This volume investigates the scope for pursuing sustainable objectives in public procurement of food and catering services, examining different regulatory contexts and organisational models to answer the overall question of how to integrate sustainability concerns into the various phases of public food procurement processes. Contributions in the book examine the policy and legal procurement framework and practices for sustainable public catering in three EU Member States: Italy, France and Spain. There is a comparative survey of the Baltic Region, including Denmark, Estonia, Finland, Poland and Russia, and moving beyond the EU, there is examination of the UK and Brazil, as well as a cross country comparison of the UK with Denmark and Sweden. Drawing on the expertise of an interdisciplinary and intersectoral team of contributors allows the book to benefit from the insights of different disciplines, including business sciences, anthropology and law. Tapping into the global discussion on public food procurement as a means to achieve multiple social and environmental goals, this work will stimulate readers looking for new creative ways to create value through public food purchasing. This book will be of great interest to students, researchers, policymakers and public- and private-sector representatives interested in public procurement, food policy and law, sustainable food sourcing and supply chain management.
English
Keywords: Agriculture & related industries; Applied ecology; Central government policies; Food & beverage technology; Food & society; sustainable,sustainability,food,procurement,legal,social,organisational